Hubungan Tingkat Kecemasan Terhadap Indeks Prestasi Kumulatif Mahasiswa Fakultas Kedokteran Universitas Pembangunan Nasional "Veteran" Jakarta - Rafilah Khansa (2023)
Anxiety is a psychological disorder that often occurs in adolescents and adults. Anxiety can affect learning outcomes by producing confusion and distortion of perception which will reduce the ability to concentrate and reduce memory. The source of anxiety in medical students consists of three main factors, namely academic pressure, social problems, and financial problems. Anxiety can inhibit cognitive function so that it affects student performance in exams and has an impact on academic achievement of medical students. This study aims to determine the correlation between the level of anxiety and the cumulative grade point average of students at the Faculty of Medicine at the Pembangunan Nasional "Veteran" Jakarta University. This research is a descriptive analytic study with a cross-sectional approach and stratified random sampling method. The sample for this study was 227 students from the 2019, 2020, and 202 batches. The research instrument used the HARS anxiety questionnaire. The statistical test used for univariate analysis was the Chi-Square test and bivariate analysis used the Chi-Square test, the Mann Whitney test, and the Annova test. From the results of the bivariate test, it was found that the p-value between the level of anxiety and the Grade Point Average value was 0.663. The results of this study indicate that there is no relationship between the level of anxiety and the cumulative grade point average of students at the Faculty of Medicine at the Pembangunan Nasional "Veteran" Jakarta University. However, there is a correlation between anxiety levels and gender.